DEVELOPING CROSS CULTURAL UNDERSTANDING-BASED INDONESIA LANGUAGE MATERIAL FOR SOUTH KOREA FOREIGN SPEAKERS - Goziyah Goziyah; Ariyana Ariyana; Kamiri Kamiri; Ira Anisa Purawinangun; Agus Sulaeman; Nanda Saputra (University of Kuningan, 2022)
The purpose of this study is to develop BIPA teaching materials based on cross-cultural and local wisdom in Banten Province. This research uses a model design for developing Indonesian language teaching materials for foreign speakers and combines existing models. The object being analyzed is the Borg and Gall’ model (1983), from the analyzed model, a modified model can be formulated. The research data are numerical data and verbal data (interview transcripts, analysis results of teaching materials, questionnaires, observations, and notes, comments, criticisms or suggestions from test subjects). The research data are numerical data and verbal data (interview transcripts, analysis results of teaching materials, questionnaires, observations, and notes, comments, criticisms or suggestions from test subjects). Given the data obtained in the form of numerical data and verbal data, the analysis was carried out in the form of quantitative analysis and qualitative analysis. The results of this study are in the form of beginner level cross-cultural based BIPA teaching materials using a contextual-communicative approach. In this case the culture used as a reference is the local culture of Banten considering that in Banten there are foreign nationals from South Korea. The results showed that the average expert trial score reached 86%, the practitioner trial score average reached 89%, and the field stage trial score averaged 87%. Therefore, this book can be categorized as very feasible to be applied.